Alkaline phosphatase in boar sperm function. (19th November 2013) - Bucci, D.; Isani, G.; Giaretta, E.; Spinaci, M.; Tamanini, C.; Ferlizza, E.; Galeati, G.
Summary Alkaline phosphatase (AP) catalyses the detachment of phosphate residues from different substrates. Its activity has been demonstrated in seminal plasma and spermatozoa from porcine and other mammalian species; anyway, the role of AP in male reproduction has not been clarified yet and the aim of this study was to determine AP function in boar sperm capacitation and in vitro fertilization (IVF). AP activity was assayed in seminal plasma and in uncapacitated and in vitro capacitated (IVC) spermatozoa; in addition, capacitation was studied in presence of different doses of AP (1.2 and 2.5 IU/mL). The effect of different doses of AP (1.2 and 2.5 IU/mL) on several sperm parameters after IVC (viability, acrosome integrity with FITC‐PSA, capacitation status with CTC staining, tyrosine phosphorylation) and on fertilizing ability during IVF were also evaluated. High AP activity was detected in seminal plasma, in particular in sperm‐rich fraction; a lower activity was detected in uncapacitated spermatozoa while a significant decrease was evidenced after IVC. Viability was not changed by AP supplementation of the capacitating medium, whereas acrosome integrity and capacitation status were significantly affected by 1.2 and 2.5 doses, with a dose‐dependent decrease in acrosome‐reacted cells as well as in CTC B pattern displaying cells. As for sperm head protein phosphorylation, a decrease in relative fluorescence was detected in AP 2.5 group, if compared with capacitated one. After IVF, a dose‐dependent decrease in penetrated oocytes was recorded, with an increase in monospermic zygote rate. In conclusion, we demonstrated that AP activity decreases under capacitating condition and that addition of AP to spermatozoa during capacitation results in a depression of the capacitating process and IVF. We can infer that AP plays a role in keeping spermatozoa quiescent until they are ejaculated and in modulating the acquisition of the fertilizing ability.